A Scoping Review on Use of Drugs Targeting the JAK/STAT Pathway in Psoriasis - Gómez-García, Francisco; Gómez-Arias, Pedro Jesús; Montilla-López, Ana; Hernández-Parada, Jorge; Sanz-Cabanillas, Juan Luís; Ruano, Juan; Parra-Peralbo, Esmeralda (Frontiers in Medicine, 2022)
Introduction The Janus kinase–signal transducer and activator of transcription (JAK/STAT) pathway are known to be involved in inflammatory immune-mediated skin diseases, including psoriasis. The development of drugs targeting the JAK/STAT signaling pathway presents new treatment opportunities for psoriasis. However, the application of JAK inhibitors for the treatment of dermatological disorders is still in its early stages of development. This review summarizes available evidence in an attempt to identify knowledge gaps for conducting further research studies and improving clinical decision-making. Objective The objective of this study is to conduct a scoping review of the use of drugs targeting the JAK/STAT pathway in the treatment of psoriasis. Methods A priori protocol for scoping review was published in 2019. The Joanna Briggs Institute Reviewer's Manual and the PRISMA Extension for Scoping Review were used for the review. MEDLINE, EMBASE, CINAHL, Scopus, and Web of Science databases and ClinicalTrials registry were referred to in April 2019 and March 2021, respectively. References in English involving evidence on the use of drugs targeting the JAK/STAT pathway in patients with psoriasis were included. Data charting was performed by two authors using tables and figures. Results The evidence found on the efficacy and safety of drugs targeting the JAK/STAT pathway in patients with psoriasis comes from 118 articles reporting the results of 34 randomized clinical trials (RCTs). Nine different drugs administered through various routes were identified (systemic: peficitinib, baricitinib, solcitinib, itacitinib, abrocitinib, deucravacitinib, and brepocitinib; topical: ruxolitinib; and both: tofacitinib). Knowledge articles are mainly created and published by pharmaceutical companies and authors through their own funding or by those related to them. Only tofacitinib and deucravacitinib have undergone phase III clinical trials, being the only ones tested with active comparators etanercept and apremilast, respectively. Proportions of Psoriasis Area and Severity Index (PASI) and Physician's Global Assessment (PGA) were the efficacy variables most frequently studied in systemic treatments. Only two RCTs declared the safety data collected by systematic assessment; the only systemic drug with phase III data was tofacitinib. Tofacitinib 5 mg two times daily (BID)/10 mg BID efficacy was compared with etanercept 50 mg/week and a placebo. At 12–16 weeks, PASI 75/PGA 01 ranges were as follows: 38.07–80%/37.16–67.4% for tofacitinib 5 mg BID; 54.79–100%/50–75.6% for tofacitinib 10 mg BID; 58.8/66.8% for etanercept, date from one only study; and 0–33.3%/9.04–33.3% for the placebo group. Other drugs in earlier stages of development showed values within these ranges. The most frequent adverse events (AEs) were nasopharyngitis and upper respiratory tract infections in all treatment groups. Conclusion There is increasing evidence on the use of drugs targeting the JAK/STAT pathway as a treatment for psoriasis, although they are in the early phases of development. The trials conducted to date have been financed directly or indirectly by the pharmaceutical industry, which must be taken into account when interpreting the results of the trials. Psoriasis treatment is currently symptomatic and could potentially present a significant risk of toxicity. Therefore, the design of principal efficacy outcome measures considering the impact of the outcome on quality of life and a drug assessment methodology aimed at improving safety would probably strengthen the evidence and decision-making process.